Long-term neuropsychiatric symptoms in spontaneous intracerebral haemorrhage survivors. Issue 3 (2nd November 2021) - Scopelliti, Giuseppe; Casolla, Barbara; Boulouis, Grégoire; Kuchcinski, Gregory; Moulin, Solène; Leys, Didier; Henon, Hilde; Cordonnier, Charlotte; Pasi, Marco
Abstract : Objective: Neuropsychiatric (NP) symptoms are prominent features of cognitive decline, but they have been understudied in patients with spontaneous intracerebral haemorrhage (ICH). In ICH survivors, we aimed at assessing NP symptoms prevalence and profiles, and their influence on long-term outcomes. Methods: We analysed data from consecutive 6-month ICH survivors enrolled in the Prognosis of Intracerebral Haemorrhage study. We performed NP evaluation using the Neuropsychiatric Inventory Questionnaire. Patients underwent long-term clinical follow-up after ICH (median follow-up time 7.2 years, IQR 4.8–8.2). Results: Out of 560 patients with ICH, 265 survived at 6 months. NP evaluation 6 months after ICH was feasible in 202 patients. NP symptoms were present in 112 patients (55%), and in 36 out of 48 patients (75%) with post-ICH dementia. Affective symptoms were present in 77 patients (38%), followed by vegetative symptoms (52 patients, 26%) and hyperactivity (47 patients, 23%). Apathy and hyperactivity were associated with post-ICH dementia and cerebral amyloid angiopathy MRI profile (all p<0.05). Apathy and hyperactivity prevailing over affective symptoms at 6-month follow-up were associated with higher risks of developing new-onset dementia (HR 5.40; 95% CI 2.27 to 12.84), while presence or severity of NP symptoms were not. Conclusion: NP symptoms were present in more than half of 6-month ICH survivors, with higher prevalence and severity in patients with post-ICH dementia. Distinctive NP profile might be associated to cognitive status and inform on long-term dementia risk.